91.2k views
1 vote
The expression below is the factorization of which of the following trinomials? (5x+2)(x-3)

2 Answers

5 votes

Use the foil method:

5x·x - 5x·3 + 2·x - 2·3

Now you have:

5x^2 - 15x + 2x - 6

= 5x^2 - 13x - 6 this is the answer

User Naveen Avidi
by
6.0k points
1 vote

The product of the given factors can be found using the distributive property.

... (5x +2)(x -3 = 5x(x -3) + 2(x -3)

... = 5x² -15x +2x -6 . . . . . this has two like terms that can be combined

... = 5x² -13x -6

User Bryan Ashley
by
5.2k points